CHALLENGES OF USING TELEHEALTH IN TRACKING TUBERCULOSIS HIV AIDs PATIENTS: A SYSTEMATIC REVIEW - Amirudin, Ikhwan; Waluyo, Agung; Nursasi, Astuti Yuni (Universitas Aisyah Pringsewu, 2024)
Lost to follow-up (LTFU) in the treatment process for HIV AIDS patients suffering from Tuberculosis is a serious problem that is a challenge for health services. This condition needs to be managed well so it must be treated immediately because the problem of Tuberculosis will have an impact not only on the sufferer himself but also cause an increase in the spread and transmission to other people. Handling the problems of HIV AIDS with tuberculosis infection needs to be managed well to ensure the implementation of the treatment process, to minimize the risk of dropping out. It is hoped that the use of digital applications in the form of telehealth will be able to have an effective function in controlling and integrating the treatment process being undertaken by HIV AIDS sufferers with tuberculosis infection. This systematic review aims to identify and provide a critical assessment. It is also to find evidence based on published articles, and carry out a synthesis of the articles obtained. This method uses a search process carried out through 5 databases (Ebsco Host, Proquest, Medline, PubMed, Cochrane), articles in English, published in 2014-2024 which were assessed by using JBI (Joanna Briggs Institute) as a guide in synthesizing the results searched and reviewed using PRISMA For Systematic reviews. The results obtained were 10 studies that described the use of digital or telehealth applications to combine adherence and loss to follow-up cases in tuberculosis treatment. The use of telehealth can contribute to overcoming the problem of patients who are lost to follow-up and increasing adherence to HIV AIDS treatment with tuberculosis infection.